Implementing mental health in practice : strategies to engage patients and families. Self-harm and suicide - Bauer, Nerissa S.; American Academy of Pediatrics ([Elk Grove Village, Illinois] : American Academy of Pediatrics, 2015)
This video focuses on using motivational interviewing techniques to identify and address self-harm and suicide. In the case demonstrated, Jennifer is a 15-year-old you have known since infancy. At her check-up, her mother expresses concern that her grades in school are declining and that she seems depressed. Jennifer doesn't want you to notice she is wearing a long-sleeve shirt, despite 90 degree weather.
Presenter: Nerissa S. Bauer.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 19, 2020)
Keywords: Teenagers -- Suicidal behavior; Parasuicide; Documentary films; Educational films; Nonfiction films; Internet videos; Streaming video; Short films